Analysis of temperature dependent dark current mechanisms for long-wavelength infrared p-on-n HgCdTe detectors. (20th April 2021) - Li, Xun; Wang, Xi; Lin, Chun; Wei, Yanfeng; Zhou, Songmin; Sun, Quanzhi
Abstract: The dark current density versus voltage ( J – V ) curve of long-wavelength infrared (LWIR) p-on-n mercury cadmium telluride (HgCdTe, MCT) photodiode is measured in the temperature range of 40 K–130 K in this study. The dark current mechanisms, namely diffusion, generation–recombination (GR), trap-assisted tunneling, band-to-band tunneling (BBT) and shunt current, are investigated for LWIR p-on-n MCT diode at different temperatures. The results show that the dark current is dominated by diffusion current at low reverse bias when the operating temperature is above 65 K. As the operating temperature decreases, GR current and shunt current gradually become the main ingredient of dark current. In the high reverse bias region, the contribution of BBT mechanism accounts for the largest proportion when the operating temperature is below 75 K. The extracted fitting parameters show that the donor concentration in the n-type region of p-on-n MCT diode display better temperature stability compared with that of n-on-p diodes. Because the thermal excitation effect increases with the increase of temperature, the equivalent trap level moves from shallow acceptor level to deep acceptor level, and the trap density increases from 1.1 × 10 10 to 6.0 × 10 12 cm −3 when the operating temperature is increased from 80 K to 130 K.